Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am a little confused proving this theorem (for $p$-forms on $M^n$, $M^n$ is a smooth manifold): $L_X\cdot i_Y-i_Y\cdot L_X=i_{[X,Y]}$ where $X,Y$ are smooth vector fields.

Now it is clear that both sides are anti-derivations, since $L_X$ is a derivation, $i_Y$ and $i_{[X,Y]}$ are anti-derivations.

Now this reduces the problem to proving that the theorem is true for $f\in C^\infty$ and $df$ for such $f$.

It seems to me the the L.H.S is zero for both $f$ and $df$.

For $f$:

L.H.S $=0$ is trivial since $i_Y$ for any zero-form is $0$

for $df$

$$i_Y \, df=df(Y) \implies L_X(i_Y \, df)=L_X(df(Y))$$


$$L_X(df)=dL_X(f) \implies i_Y(L_X(df))=L_X(df)(Y)$$

Hence L.H.S. $=0$

Have I made an error here ?

Thanks for any help or pointers.

share|cite|improve this question
I follow the first part of your question, but I think that since we have that $i_X: \Omega^{n} \to \Omega^{n-1}$ is definition of interior product, the result follows since $i_X df= f$ and since all zero-forms are trivially zero (need it for the Lie algebra) LHS vanishes. – Jaivir Baweja Jan 30 '13 at 22:58
@JaivirBaweja what makes you think that $i_X df = f$? – ZulfiqarIII Jan 30 '13 at 23:01
@nonlinearism for $f$ the rhs also vanishes, so that's good. However, $L_X( df(Y) ) \neq L_x(df)(Y)$ (the first one being the Lie derivative of the function $df(Y)$, the second one being the 1-form $L_X(df)$ evaluated at $Y$), so your second conclusion does not hold. – ZulfiqarIII Jan 30 '13 at 23:03
Why should $(L_X (df))(Y) = L_X (df(Y))$? – Eric O. Korman Jan 30 '13 at 23:38
up vote 1 down vote accepted

As per my comment, $(L_X (df))(Y) \ne L_X (df(Y))$? One way to prove what you want is to use the fact that Lie differentiation satisfies the Leibniz rule with respect to contraction: $$ L_X(df(Y)) = (L_X df)(Y) + df L_X Y = i_Y L_X(df) + i_{[X,Y]} df. $$ Subtracting off $i_Y L_X(df)$ gives the right hand side.

share|cite|improve this answer
Thanks Eric, I see my error. – nonlinearism Jan 31 '13 at 21:14

Here's an alternative approach to this question.

Let $\alpha$ be a $p$-form, and let $\phi_t$ be the flow along $X$. By definition $$L_X i_Y(\alpha) = \left\{ \dfrac{d}{dt}\phi_t^* (i_Y \alpha) \right\}_{t=0} = \left\{ \dfrac{d}{dt} i_{\phi_t^* Y} (\phi_t^* \alpha) \right\}_{t=0}$$ so by the chain rule and linearity of $Y \mapsto i_Y$ we find $$L_X i_Y(\alpha) = i_{ L_X Y } \alpha + i_Y L_X \alpha.$$ Since $L_X Y = [X,Y]$ this proves the claim.

share|cite|improve this answer
Yup, I got it, thanks! – nonlinearism Jan 31 '13 at 21:14

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.